Creative Union : The Professional Organization of Soviet Composers, 1939-1953 - Tomoff, Kiril (Book collections on Project MUSE., 2006)
Central to Tomoff's argument is the institutional authority and prestige that the musical profession accrued and deployed within Soviet society, enabling musicians to withstand the postwar disciplinary campaigns that were so crippling in other artistic and literary spheres."--Jacket.